Simulation of Loading Policies in the Virtual-Build-to-Order Fulfillment System for Automotive Industry - Hui, Peng (2006)
As companies race to adopt mass customization (MC) as one of the key strategies, it becomes increasingly important to understand how order fulfillment system work more effectively and efficiently. Within the automotive sector, virtual-build- to-order (VBTO) is an emerging form of order fulfillment system that attempts to achieve high fulfillment performance level to reduce customers waiting time and minimize the finished product stock. Its suitability for use has been identified as part or a MC manufacturing strategy, in particular for the Catalogue Mode of MC. An automaker in this position would need to understand the relationships between system variables.